What Fuels the Boom Drives the Bust : Regulation and the Mortgage Crisis - Dagher, Jihad (IMF Working Papers; Working Paper ;, 2011)
We show that the lightly regulated non-bank mortgage originators contributed disproportionately to the recent boom-bust housing cycle. Using comprehensive data on mortgage originations, which we aggregate at the county level, we first establish that the market share of these independent non-bank lenders increased in virtually all US counties during the boom. We then exploit the heterogeneity in the market share of independent lenders across counties as of 2005 and show that higher market participation by these lenders is associated with increased foreclosure filing rates at the onset of the housing downturn. We carefully control for counties' economic, demographic, and housing market characteristics using both parametric and semi-nonparametric methods. We show that this relation between the pre-crisis market share of independents and the rise in foreclosure is more pronounced in less regulated states. The macroeconomic consequences of our findings are significant: we show that the market share of these lenders as of 2005 is also a strong predictor of the severity of the housing downturn and subsequent rise in unemployment. Overall our findings lend support to the view that more stringent regulation could have averted some of the volatility on the housing market during the recent boom-bust episode.